Correlations of Clinical and Laboratory Measures of Balance in Older Men and Women: The MOBILIZE Boston Study - Nguyen, Uyen-Sa D.T. (2012)
OBJECTIVE: Impaired balance is associated with falls in older adults. However, there is no accepted gold standard on how balance should be measured. Few studies have examined measures of postural sway and clinical balance concurrently in large samples of community-dwelling older adults. We examined the associations among four types of measures of laboratory- and clinic-based balance in a large population-based cohort of older adults. METHODS: We evaluated balance measures in the MOBILIZE Boston Study (276 men, 489 women, 64–97 years). Measures included: (1) laboratory-based anteroposterior (AP) path length and average sway speed, mediolateral (ML) average sway and root-mean-square, and area of ellipse postural sway; (2) Short Physical Performance Battery (SPPB); (3) Berg Balance Scale; and (4) one-leg stand. Spearman Rank Correlation Coefficients (r) were assessed among the balance measures. RESULTS: Area of ellipse sway was highly correlated with the ML sway measures (r >0.9, p < 0.0001), and sway speed was highly correlated with AP sway (r=0.97, p < 0.0001). The Berg Balance Scale was highly correlated with SPPB (r=0.7, p<0.001), and one-leg stand (r=0.8, p<0.001). Correlations between the laboratory- and clinic-based balance measures were low but statistically significant (0.2 < r < 0.3, p<0.0001). CONCLUSION: Clinic-based balance measures, and laboratory-based measures comparing area of ellipse with ML sways or sway speed with AP sway, are highly correlated. Clinic- with laboratory-based measures are less correlated. As both laboratory- and clinic-based measures inform balance in older adults but are not highly correlated with each other, future work should investigate the differences.